2020
DOI: 10.1177/1045389x20943948
|View full text |Cite
|
Sign up to set email alerts
|

Internal magnetic field tests and magnetic field coupling model of a three-coil magnetorheological damper

Abstract: Magnetorheological damper is a typical semi-active control device. Its output damping force varies with the internal magnetic field, which is a key factor affecting the dynamic performance of the magnetorheological dampers. Existing studies about the magnetic field of magnetorheological dampers are limited to theoretical analysis; thus, this study aims to experimentally explore the complicated magnetic field distribution inside the magnetorheological dampers with multiple coils. First, the magnetic circuit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…When the current comes 0 A the yield strength does not disappear, which means the MRF keeps a certain inherent yield strength [28]. The saturation characteristics at high level current cases and the inherent yield characteristics at zero-field are consistent with previous research [29]. The identification of F y has the following presentation…”
Section: Parameter Identificationsupporting
confidence: 86%
“…When the current comes 0 A the yield strength does not disappear, which means the MRF keeps a certain inherent yield strength [28]. The saturation characteristics at high level current cases and the inherent yield characteristics at zero-field are consistent with previous research [29]. The identification of F y has the following presentation…”
Section: Parameter Identificationsupporting
confidence: 86%
“…The modified two‐column model for the MR fluid proposed above can finely describe relationship between the yield shear stress of the MR fluid and the magnetic induction intensities. The variation of the magnetic induction intensity with current can be revealed in the magnetic field coupling model for the three‐coil MR dampers proposed in a previous study about the magnetic field distribution of the three‐coil MR dampers, 34 as shown in Equation 9, BE=()0.916I0.048italicNIμ0μ()D+h·ln[]D+2hD,0.5emBI=()1.264I0.177italicNIμ0μ()D+h·ln[]D+2hD, in which B E is the magnetic induction intensities for the external damping gap and B I is the magnetic induction intensities for the internal damping gap. Combining the modified two‐column for the MR fluid and the magnetic field coupling model for the three‐coil MR damper, the relationship between the yield shear stress and the excitation current can be expressed as follows: τyE=[]12Ar3χ2BE2φ5μ0()1+χ12()2r+2t3D()n+τ0,τyI=[]12Ar3χ2BI2φ5μ0()1+χ12()2r+2t3D()n+τ0, in which τ yE is the yield shear stress of the MR fluid of the external damping gap and τ yI is the yield shear stress of the MR fluid of the internal damping gap.…”
Section: Modified Micromodel Of the Mr Fluidmentioning
confidence: 98%
“…The modified two-column model for the MR fluid proposed above can finely describe relationship between the yield shear stress of the MR fluid and the magnetic induction intensities. The variation of the magnetic induction intensity with current can be revealed in the magnetic field coupling model for the three-coil MR dampers proposed in a previous study about the magnetic field distribution of the three-coil MR dampers, 34 as shown in Equation 9,…”
Section: Experimental Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanthakumar, A J D et al [22] carried out fluid flow principled analysis and electromagnetic flux analysis for the more important parameters such as fluid and magnetic flux of the magnetorheological damper and finally calculated the damping force generated by the damper. Yang Yang,and Zhao-Dong Xu et al [23]. Studied the complex magnetic field distribution in the case of magnetorheological dampers with three coils.…”
Section: Introductionmentioning
confidence: 99%